The Impact of Customer Retention Orientation and Brand Orientation on Customer Loyalty and Financial performance in SMEs: Empirical Evidence from a Balkan Country - Ciunova shuleska, Anita; Palamidovska sterjadovska, Nikolina; Osakwe Nedu Christian; Omotoso, J (Journal of East European Management Studies, 2017)
The goal of this paper is to explore the impact of SMEs’ strategic orientations on customer loyalty and financial performance. SEM analysis was employed in order to test the proposed hypotheses. Our study suggests that SMEs can improve their customer loyalty performance by developing their orientation toward creating customer retention and brand value, while at the same time maintaining brand consistency. The results confirmed only the positive relationship between brand orientation and financial performance partially mediated by customer loyalty. The type of business sector and the company’s size as control variables do not affect the assumed relationships in the model.
Keywords: brand consistency, customer loyalty performance, brand orientation, customer retention orientation, financial performance, SMEs